1992
DOI: 10.1111/j.1348-0421.1992.tb02084.x
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Method for Overproduction and Purification of p24 Gag Protein of Human Immunodeficiency Virus Type 1

Abstract: A simple method for the overproduction in Escherichia coli and purification of major core protein p24 of human immunodeficiency virus type 1 (HIV-1) was described. The gag-pol region encoding p24, p15, and protease was fused to 3' end of lacZ gene on plasmid. A LacZ-Gag fusion protein, the major primary product, is designed to be cleaved by the HIV-1 protease coexpressed through frameshifting. In fact, p24 and its immediate precursor, p25, were produced in the cells grown at 25 C, but not at 37 C. When the gag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

1995
1995
2000
2000

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…The Gag-Pol proteins, which were synthesized through frameshifting as the minor products, containing the entire protease moiety, had the protease activity and could process the Gag proteins synthesized as major products and themselves in E. coli (39,43). However, the protease synthesized via frameshifting could not process the Gag proteins completely.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Gag-Pol proteins, which were synthesized through frameshifting as the minor products, containing the entire protease moiety, had the protease activity and could process the Gag proteins synthesized as major products and themselves in E. coli (39,43). However, the protease synthesized via frameshifting could not process the Gag proteins completely.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have reported that the gag-to-pol frameshifting occurred during the translation of the gag gene in E. coli, as in the virus-infected cells (38,39,43). The Gag-Pol proteins, which were synthesized through frameshifting as the minor products, containing the entire protease moiety, had the protease activity and could process the Gag proteins synthesized as major products and themselves in E. coli (39,43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recombinant p24 (rp24) was produced in Escherichia coli transformed with expression plasmid carrying the corresponding cDNA and was purified as described previously (12). The recombinant proviral clone used was pNL4-3 (13), which contained DNA from HIV-1 isolates NY5 (GenBank accession number HIVNL43) and LAV (14), and the sequences for rp24 derived from NY5.…”
Section: Recombinant Proteins Of Hiv-1mentioning
confidence: 99%
“…Recombinant HIV-1 p17 (rp17) and p24 (rp24) antigens were produced in Escherichia coli transformed with expression plasmids carrying the corresponding cDNAs and were purified as described previously (28,31). The recombinant proviral clone used was pNL4-3 (1), which contained DNA from HIV-1 isolates NY5 (GenBank accession no.…”
Section: Methodsmentioning
confidence: 99%